The Cohesion Analysis of Students’ Multimodal Text Creations - Ika Anggraeni; Didin Nuruddin Hidayat; Nida Husna; Alek Alek; Abdul Halim (Edukasi, 2023)
Examining cohesion of students’ compositions (e.g., students’ thesis writing, narratives) has been conducted by many researchers, yet cohesion of students’ multimodal text creations (a picture with captions) is still paucity. Therefore, this study aims to fill the research gap by examining the cohesion of students’ multimodal text creations using grammatical cohesive devices proposed by Halliday and Hasan (2014a) and inter-semiotic cohesive devices proposed by Liu and O’Halloran (2009). The students’ caption text analysis showed that students use three cohesive grammatical devices: references at 49%, conjunctions at 46%, and substitution at 5%. The most frequent types of them used by the students are personal references at 76%, additive conjunction at 63%, and clausal substitution at 67%. In addition, the analysis of inter-semiotic cohesive devices shows that parallel structure is hardly found in multimodal texts. Still, surprisingly, inter-semiotic polysemy is utilized by students to create co-contextualize relationships between language and images and experiential convergence. The study concluded that students in the twelfth grade of Nurul Huda Vocational High School lack using various cohesive devices. Nonetheless, they complement their caption with inter-semiotic cohesive devices embedded in the images. This study implies that the students still need more time allocation to study the subject at hand and go through the writing process as professionals do to create a better text for more elaboration and characteristics of written language with accuracy and consistency.